The art of yoik in care: Sami caregivers' experiences in dementia in Northern Norway - Hämäläinen, Soile; Musial, Frauke; Graff, Ola; Schirmer, Henrik; Salamonsen, Anita; Mehus, Grete (Nordic Journal of Arts, Culture and Health, 2020)
Purpose : Yoik is the traditional vocal art of the Sami, the indigenous people of Fennoscandia. The Sami people, their land and their culture have been subject to colonisation and assimilation for centuries, hence the practice of yoik was lost in many regions. Despite an increasing awareness of the benefits of health musicking, yoik is only sporadically included in musicking practices in dementia care contexts. Therefore, the purpose of this study is to explore Sami caregivers’ yoik experiences in formal and informal care contexts. Design : Qualitative in-depth semi-structured interviews with 17 Sami relatives of care receivers, and healthcare professionals. Qualitative content analysis from subthemes to main themes was used to identify themes. Findings : The research revealed two key findings: 1) yoik enlivens, empowers, induces “good feelings” and enables reminiscence functions in elderly persons with dementia or impaired overall functioning, 2) yoik is not systematically applied in in-care contexts due to the history and consequences of assimilation and colonisation. Originality/value : This study explores some of the consequences of colonisation and assimilation on healthcare services and provides insights into an under-researched topic, the function of yoik as a music-based practice for the well-being of older adults. The study reveals that yoik can act as an attunement tool. Yoik may manifest and enhance connectedness to oneself, to the natural environment and to the community. This type of attunement lies at the heart of person-centered care.